2020
DOI: 10.3389/fnins.2020.00414
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NMDA Receptors in the Effect of Purinergic P2X7 Receptor on Spontaneous Seizure Activity in WAG/Rij Rats With Genetic Absence Epilepsy

Abstract: P2X7 receptors (P2X7Rs) are ATP sensitive cation channels and have been shown to be effective in various epilepsy models. Absence epilepsy is a type of idiopathic, generalized, non-convulsive epilepsy. Limited data exist on the role of P2X7Rs and no data has been reported regarding the interaction between P2X7Rs and glutamate receptor NMDA in absence epilepsy. Thus, this study was designed to investigate the role of P2X7 and NMDA receptors and their possible interaction in WAG/Rij rats with absence epilepsy. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
2
11
0
Order By: Relevance
“…4c d). This is consistent with previous findings that both P2X7 receptor and SFKs have functional interaction with NMDA receptor respectively in different models of neurological diseases [29,30]; Notably, functional interaction between NR2A-containing NMDA receptor and SFKs mediates CSD as evidenced by that the SFK activator, pYEEI restored the inhibitory effect of NR2A-containining NMDA receptor antagonist on CSD in mouse brain slices [21]. These data suggest that P2X7 receptor/SFKs signaling-mediated CSD is likely to be dependent on NMDA receptor activity.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…4c d). This is consistent with previous findings that both P2X7 receptor and SFKs have functional interaction with NMDA receptor respectively in different models of neurological diseases [29,30]; Notably, functional interaction between NR2A-containing NMDA receptor and SFKs mediates CSD as evidenced by that the SFK activator, pYEEI restored the inhibitory effect of NR2A-containining NMDA receptor antagonist on CSD in mouse brain slices [21]. These data suggest that P2X7 receptor/SFKs signaling-mediated CSD is likely to be dependent on NMDA receptor activity.…”
Section: Discussionsupporting
confidence: 94%
“…Series 3: As P2X7 receptor exhibits functional interaction with NMDA receptor in neurons and a rat epilepsy model [29,30], while SFKs regulate NMDA receptor activity and function [31], both of which are required for CSD propagation [8,32,33], we then explored the involvement of NMDA receptor in SFKs-mediated P2X7 receptor signaling during CSD.…”
Section: Induction and Recording Of Csd By Intrinsic Optical Imaging In Mouse Brain Slices And Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no effect of P2X 7 antagonism on seizures was observed in WAG/Rij rats, a model of genetic absence epilepsy. 10 Suggesting a proconvulsive function of the P2X 7 receptor, Kim and Kang reported exacerbated seizure severity in P2X 7 -KO mice using a pilocarpine (150,175,200,225, or 250 mg/kg, IP) mouse model. 205 In addition, research by the same group using the pilocarpine (380 mg/kg, IP) rat model showed that P2X 7 antagonism (oxidized ATP [OxATP] and BBG) protected against astroglial cell death, 206 reduced the infiltration of neutrophils into the frontoparietal cortex, 207 and increased status epilepticus-induced hippocampal neurodegeneration.…”
Section: Targeting Of P2x Receptors During Seizures and Epilepsymentioning
confidence: 99%
“…1 Hippocampal sclerosis, characterized by a pattern of selective neuronal loss and reactive gliosis, is the most common pathological finding in brains of TLE patients. 9 Of note, whereas some recent studies have investigated a potential role of ATP-gated P2 receptors in epilepsies with a genetic cause (eg, use of WAG/Rij rats, which is a model of genetic absence epilepsy 10 ), most effort has been invested in studying these receptors in TLE, 11 which is thus the main focus of the present review. While there are several options for the treatment of epilepsy, which include brain surgery, use of the ketogenic diet, or vagus nerve/deep-brain stimulation, antiseizure medication remains the first-choice treatment of epilepsy, with over 25 antiseizure drugs (ASDs) available.…”
Section: Introductionmentioning
confidence: 99%